Organics and fertility levels influences barley yield and soil properties in semi-arid region of Rajasthan - Kumawat, Sita; Sharma, S. R.; Rundala, S. R.; Dogra, Prerna (Annals of Agricultural Research, 2016)
A field experiment was conducted for two consecutive rabi (winter) seasons of 2011-12 and 2012-13at the Agronomy Farm of S.K.N. College of Agriculture, Jobner, Rajasthan to evaluate the effect oforganics and fertilizer levels on barley yield and soil bio-chemical properties. The application ofvermicompost @ 5 t ha-1 + biofertilizers significantly increased the grain yield of barley by 29.23%,mean over two years of study. Addition of FYM and vermicompost alone or in combination withbiofertilizers showed significant improvement in soil nutrient availability, dehydrogenase andalkaline phosphatase activities and microbial biomass carbon, nitrogen and phosphorus afterharvesting of barley over control. Among the organics, the application of vermicompost @ 5 t ha-1 +biofertilizers recorded improvement in all the soil properties. Fertilizing the crop with 75% RDFgave significantly highest grain yield of barley over unfertilized plots. Application of increasinglevels of chemical fertilizers also improved the soil bio-chemical properties over control.